Endogenous CCN5 Participates in Angiotensin II/TGF-β1 Networking of Cardiac Fibrosis in High Angiotensin II-Induced Hypertensive Heart Failure - Huang, Anan; Li, Huihui; Zeng, Chao; Chen, Wanli; Wei, Liping; Liu, Yue; Qi, Xin (Frontiers in Pharmacology, 2020)
Aberrant activation of angiotensin II (Ang II) accelerates hypertensive heart failure (HF); this has drawn worldwide attention. The complex Ang II/transforming growth factor (TGF)-β1 networking consists of central mechanisms underlying pro-fibrotic effects; however, this networking still remains unclear. Cellular communication network 5 (CCN5), known as secreted matricellular protein, mediates anti-fibrotic activity by inhibiting fibroblast-to-myofibroblast transition and the TGF-β1 signaling pathway. We hypothesized that endogenous CCN5 plays an essential role in TGF-β1/Ang II networking-induced cardiac fibrosis (CF), which accelerates the development of hypertensive HF. This study aimed to investigate the potential role of CCN5 in TGF-β1/Ang II networking-induced CF. Our clinical retrospective study demonstrated that serum CCN5 decreased in hypertensive patients, but significantly increased in hypertensive patients taking oral angiotensin-converting enzyme inhibitor (ACEI). A negative association was observed between CCN5 and Ang II in grade 2and 3 hypertensive patients receiving ACEI treatment. We further created an experimental model of high Ang II-induced hypertensive HF. CCN5 was downregulated in the spontaneously hypertensive rats (SHRs) and increased via the inhibition of Ang II production by ACEI. This CCN5 downregulation may activate the TGF-β1 signaling pathway, which promotes direct deposition of the extracellular matrix (ECM) and fibroblast-to-myofibroblast transition via activated Smad-3. Double immunofluorescence staining of CCN5 and cell markers of cardiac tissue cell types suggested that CCN5 was mainly expressed in the cardiac fibroblasts. Isolated cardiac fibroblasts were exposed to Ang II and transfected with small interfering RNA targeting CCN5. The expression of TGF-β1 together with Col Ia and Col IIIa was further promoted, and alpha-smooth muscle actin (α-SMA) was strongly expressed in the cardiac fibroblasts stimulated with Ang II and siRNA. In our study, we confirmed the anti-fibrotic ability of endogenous CCN5 in high Ang II-induced hypertensive HF. Elevated Ang II levels may decrease CCN5 expression, which subsequently activates TGF-β1 and finally promotes the direct deposition of the ECM and fibroblast-to-myofibroblast transition via Smad-3 activation. CCN5 may serve as a potential biomarker for estimating CF in hypertensive patients. A novel therapeutic target should be developed for stimulating endogenous CCN5 production.